When Single Parents Marry: Do Children Benefit Academically?. Issue 4 (20th February 2021) - Usevitch, Matthew T.; Dufur, Mikaela J.
Abstract : Objective: The objective of this research is to determine whether children born to single parents benefit academically if their parents marry. Background: Children born to single parents have on average worse educational outcomes than peers who live with married parents, but transitions to a married parent family are not well understood. Method: We use the U.S. Early Childhood Longitudinal Study Kindergarten Cohort of 1998 to create two groups of children born to single parents: children who remain in a stable single‐parent family ( n  = 220) and children whose single parent marries ( n  = 392). We examine differences in reading and math test scores in context of potential confounding variables. Results: Initial findings suggest that children born to single parents whose parents marry perform better than do their peers in stable single‐parent families, but this effect disappears when controls for financial and human capital, race, and stress are included. Conclusion: Financial and human capital resources explain the perceived benefit of parent marriage, suggesting benefits of marriage accrue due to selectivity factors among parents more likely to marry. Other factors, such as stress, race, and number of siblings, play a role. Implications: Determining the nature of the link between parental marriage and educational outcomes has important policy implications as to whether marriage should be promoted as an educational benefit to children.